Redescriptions of two Lestidiops species (Aulopiformes: Paralepididae) from Japan, with comments on their morphology - Ho, Hsuan-Ching; Yang, Tsung-Yu (Zootaxa, 2024)
Specimens of two barracudina species, Lestidiops sphyraenopsis Hubbs and Lestidiops ringens (Jordan & Gilbert), collected from Japan, were examined. Both species were originally described from the northeastern Pacific and are widespread in both sides of northern Pacific Ocean. Diagnoses, detailed descriptions, and complete morphological data for both species are provided. These two species exhibit several distinct features that differ from those of their congeners, and their morphological characteristics are discussed.